Neutrophil gelatinase-associated lipocalin and associated damage markers in a chronic kidney disease model and an acute muscle injury model. - Mahachi, Carol Batsirai (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.